2000
DOI: 10.4141/s99-033
|View full text |Cite
|
Sign up to set email alerts
|

Soil enzyme activities following paper sludge addition in a winter cabbage-sweet corn rotation

Abstract: M. 2000. Soil enzyme activities following paper sludge addition in a winter cabbage-sweet corn rotation. Can. J. Soil Sci. 80: 91-97. Combined primary and secondary papermill sludge (PS) is a good source of C and other nutrients for soils devoted to intensive horticultural production. A field study was conducted to evaluate the effect of PS, spring-applied alone or in combination with ammonium nitrate (AN), on the enzymatic activity of a Bedford clay (Humic Gleysol) in the province of Québec, Canada. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
7
0
2
Order By: Relevance
“…These results support the earlier studies, which also found positive effects of raw and composted de-inking sludges on soil microbial biomass and enzyme activities (Simard et al 1998bChantigny et al 2000;Gagnon et al 2000). In our study, neither acid nor alkaline phosphatase activity was significantly (r = 0.15 -0.19, P > 0.05) correlated to Mehlich-3 extractable soil P content.…”
Section: Soil Enzyme Activitiessupporting
confidence: 82%
See 1 more Smart Citation
“…These results support the earlier studies, which also found positive effects of raw and composted de-inking sludges on soil microbial biomass and enzyme activities (Simard et al 1998bChantigny et al 2000;Gagnon et al 2000). In our study, neither acid nor alkaline phosphatase activity was significantly (r = 0.15 -0.19, P > 0.05) correlated to Mehlich-3 extractable soil P content.…”
Section: Soil Enzyme Activitiessupporting
confidence: 82%
“…Kannan and Oblisami (1990) observed an increase in many enzyme activities after several years' application of raw paper mill effluents. Recently Simard et al (1998a) and Gagnon et al (2000) showed that addition of combined primary and secondary de-inking sludges improved soil enzyme activities, but that rates in excess of 32 Mg ha -1 may be detrimental.…”
mentioning
confidence: 99%
“…This amount of PS contained 111.6 kg total N. Thus, 1997 PS total N-fertiliser efficiency was estimated to be equivalent to 134%, indicating a very important residual effect of the PS added N in 1996 on the corn yield in 1997. In this study, non-nutritional effects through improvement of water availability, may have improved soil physical properties and microbial activity which in turn may also have contributed to the high fertiliser efficiency (Trepanier et al 1996;Simard et al 1998b;Chantigny et al 1999;Gagnon et al 2000).…”
Section: Sweet Corn Yieldsmentioning
confidence: 99%
“…Our objective was to determine, under field conditions, the effect of two yearly applications of combined PS on crop yield and N uptake, and to evaluate N fertiliser equivalence and N residual effects of PS. The impact of PS on soil enzyme activities was recently reported (Gagnon et al 2000).…”
mentioning
confidence: 99%
“…(1 annually, to avoid soil quality degradation through acidification, excess accumulation of major nutrients and metals, and reduced soil enzymatic activity (as compared with lower rates of sludge application) (Gagnon et al 2000Gagnon and Ziadi 2004). Increased leaching of nitrate and phosphate from excess sludge application may, in turn, lead to groundwater contamination (Gagnon and Ziadi 2004).…”
Section: Use Of Legumes Composts and Industrial Residues In Agricultmentioning
confidence: 99%